(untitled) ("Journal "U". Economy. Management. Finance.", 2023)
The article highlights 9 most important parameters for the study of integration processes, such as integration potential, volume, structure and dynamics of mutual trade turnover, structural development and complementarity of national economic systems, conditions for the movement of factors of production, interaction in the political sphere, global and intercountry conditions of economic exchange, equivalence benefits from the integration of participating countries, features of the international division of labor between countries participating in the integration process, deformation of the integration economic complex of states; the most important parameters characterizing the features of integration processes in developed and developing countries have been studied, and their comparative characteristics have been carried out.